Plasma Fibrinopeptide A and Beta-Thromboglobulin in Patients with Chest Pain - Douglas, J T; Lowe, G D O; Forbes, C D; Prentice, C R M (Thrombosis and Haemostasis, 1983)
Plasma levels of β-thromboglobulin (BTG) and fibrinopeptide A (FPA), markers of platelet release and thrombin generation respectively, were measured in 48 patients within 3 days of admission to hospital for acute chest pain. Twenty-one patients had a confirmed myocardial infarction (MI); 15 had unstable angina without infarction; and 12 had chest pain due to noncardiac causes. FPA and BTG were also measured in 23 control hospital patients of similar age. Mean plasma BTG levels were not significantly different in the 4 groups. Mean plasma FPA levels were significantly higher in all 3 groups with acute chest pain when compared to the control subjects (p < 0.01), but there were no significant differences between the 3 groups. Increased FPA levels in patients with acute chest pain are not specific for myocardial infarction, nor for ischaemic chest pain.
Keywords: Fibrinopeptide A; Beta-thromboglobulin; Chest pain